F4‐TCNQ as an Additive to Impart Stretchable Semiconductors with High Mobility and Stability - Jaewan Mun; Jiheong Kang; Yu Zheng; Shaochuan Luo; Yilei Wu; Huaxin Gong; Jian‐Cheng Lai; Hung‐Chin Wu; Gi Xue; Jeffrey B.‐H. Tok; Zhenan Bao (Advanced Electronic Materials, 2020)
Abstract Numerous strategies are developed to impart stretchability to polymer semiconductors. Although these methods improve the ductility, mobility, and stability of such stretchable semiconductors, they nonetheless still need further improvement. Here, it is shown that 2,3,5,6‐tetrafluoro‐7,7,8,8‐tetracyanoquinodimethane (F4‐TCNQ) is an effective molecular additive to tune the properties of a diketopyrrolopyrrole‐based (DPP‐based) semiconductor. Specifically, the addition of F4‐TCNQ is observed to improve the ductility of the semiconductor by altering the polymer’s microstructures and dynamic motions. As a p‐type dopant additive, F4‐TCNQ can also effectively enhance the mobility and stability of the semiconductor through changing the host polymer’s packing structures and charge trap passivation. Upon fabricating fully stretchable transistors with F4‐TCNQ‐DPP blended semiconductor films, it is observed that the resulting stretchable transistors possess one of the highest initial mobility of 1.03 cm2 V−1 s−1. The fabricated transistors also exhibit higher stability (both bias and environmental) and mobility retention under repeated strain, compared to those without F4‐TCNQ additive. These findings offer a new direction of research on stretchable semiconductors to facilitate future practical applications.